Cosmetic risk assessment of 2-((4-r-5-(thiophen-2-yl)-4h-1,2,4- triazol-3-yl)thio)acetic acid derivatives - Salionov, V. O.; Korniienko, O. O.; Саліонов, Володимир Олександрович; Корнієнко, Олена Олександрівна (My University, 2024)
The aim of the work. To assess if the studied compounds can cause 9 categories of toxicity related to eye, skin, and phototoxicity.
Keywords: тези доповідей